The Memory of Silence/Memoria del silencio - Aragon, Uva De (Book collections on Project MUSE., 2014)
A metaphor of a nation and its Diaspora, this bilingual edition of THE MEMORY OF SILENCE/MEMORIA DEL SILENCIO transcends the Cuban reality and becomes a story of universal breadth, a triumph of love and family over distance and politics. In 1959, at the age of 18, the twin sisters Lauri and Menchu share a common past, but their lives abruptly take on seemingly irreconcilable differences as Lauri leaves with her groom for Miami and Menchu remains in Havana. The text, then, becomes a series of interpolated chronicles, as each alternating chapter recounts one sister's life and then the other until finally in the present, now reunited, the sisters must confront the pain of the past and as well as the promise of the future. The novel's theme of reconciliation presents a refreshing message, and a timely one.